2012
DOI: 10.1161/circulationaha.111.040766
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Complications in Patients With Community-Acquired Pneumonia

Abstract: Background-Community-acquired pneumonia (CAP) affects Ͼ5 million adults each year in the United States. Although incident cardiac complications occur in patients with community-acquired pneumonia, their incidence, timing, risk factors, and associations with short-term mortality are not well understood. Methods and Results-A total of 1343 inpatients and 944 outpatients with community-acquired pneumonia were followed up prospectively for 30 days after presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
154
2
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(171 citation statements)
references
References 35 publications
9
154
2
6
Order By: Relevance
“…Observational epidemiological studies have confirmed what experienced clinicians suspected for many years: cardiovascular events can be triggered by a variety of common noncardiovascular clinical conditions, particularly those that are associated with systemic inflammation [1][2][3] . One of the best documented examples of non-infectious systemic inflammation causing an acute increase in cardiovascular risk is major surgery.…”
Section: Introductionmentioning
confidence: 63%
“…Observational epidemiological studies have confirmed what experienced clinicians suspected for many years: cardiovascular events can be triggered by a variety of common noncardiovascular clinical conditions, particularly those that are associated with systemic inflammation [1][2][3] . One of the best documented examples of non-infectious systemic inflammation causing an acute increase in cardiovascular risk is major surgery.…”
Section: Introductionmentioning
confidence: 63%
“…Acute lung injury and multi-organ dysfunction syndrome, as well as acute cardiac events mostly occurring early in the course of CAP, have been identified as being significant contributors to mortality [1][2][3][4][5][6][7]. In the case of pneumococcal CAP, an increasing body of evidence, derived from both clinical and experimental studies, has implicated the major cytolytic, cholesterolbinding, pore-forming protein toxin, pneumolysin (Ply), in the pathogenesis of associated adverse pulmonary and cardiovascular events [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Corrales-Medina et al (32) detected the majority of cardiovascular complications in the first week. As these complications have a very early onset, the patient may be in the emergency room, observation area, or short stay ward, thus reasserting the importance of early diagnosis and treatment in the HER but also the need for tools that help predict mortality.…”
Section: Survival Analysismentioning
confidence: 98%